Fabrication of small-diameter vascular scaffolds by heparin-bonded P(LLA-CL) composite nanofibers to improve graft patency - Wang S (Dove Medical Press, 2013)
Sheng Wang,1,* Xiu M Mo,2,* Bo J Jiang,1 Cheng J Gao,1 Hong S Wang,2 Yu G Zhuang,1 Li J Qiu21Department of Emergency and Critical Care Medicine, Shanghai Tenth People’s Hospital, Tongji University, Shanghai, People's Republic of China; 2State Key Laboratory for Modification of Chemical Fibers and Polymer Materials, Donghua University, Shanghai, People’s Republic of China *These authors contributed equally to this workAbstract: The poor patency rate following small-diameter vascular grafting remains a major hurdle for the widespread clinical application of artificial blood vessels to date. Our previous studies found that electrospun poly(L-lactide-co-epsilon-caprolactone) (P[LLA-CL]) nanofibers facilitated the attachment and growth of endothelial cells (EC), and heparin incorporated into P(LLA-CL) nanofibers was able to release in a controlled manner. Hence, we hypothesized that heparin-bonded P(LLA-CL) vascular scaffolds with autologous EC pre-endothelialization could significantly promote the graft patency rate. To construct a small-diameter vascular scaffold, the inner layer was fabricated by heparin-bonded P(LLA-CL) nanofibers through coaxial electrospinning, while the outer layer was woven by pure P(LLA-CL) nanofibers. Except dynamic compliance (5.4 ± 1.7 versus 12.8 ± 2.4 × 10-4/mmHg, P < 0.05), maximal tensile strength, burst pressure, and suture retention of the composite, scaffolds were comparable to those of canine femoral arteries. In vitro studies indicated that the scaffolds can continuously release heparin for at least 12 weeks and obtain desirable endothelialization through dynamic incubation, which was confirmed by EC viability and proliferation assay and scanning electronic microscopy. Furthermore, in vivo studies demonstrated that pre-endothelialization by autologous ECs provided a better effect on graft patency rate in comparison with heparin loading, and the united application of pre-endothelialization and heparin loading markedly promoted the 24 weeks patency rate of P(LLA-CL) scaffolds (88.9% versus 12.5% in the control group, P < 0.05) in the canine femoral artery replacement model. These results suggest that heparin-bonded P(LLA-CL) scaffolds have similar biomechanical properties to those of native arteries and possess a multiporous and biocompatible surface to achieve satisfactory endothelialization in vitro. Heparin-bonded P(LLA-CL) scaffolds with autologous EC pre-endothelialization have the potential to be substitutes for natural small-diameter vessels in planned vascular bypass surgery.Keywords: electrospinning, heparin, vascular graft, endothelialization, patency rate